KLAUSUL PERJANJIAN DALAM TRANSAKSI E-COMMERCE MELALUI INSTAGRAM DITINJAU DARI HUKUM PERIKATAN - Alya Nur Oktaviany, (2021)
ABSTRACT Currently, e-commerce transactions that are most widely used by people through social media platfor. One of them is Instagram. With the existence of e-commerce, it makes it easier for people to buy and sell online because transactions are easier, more effective, and efficient. However, in practice there are still many defaults committed by both the seller and the buyer in carrying out these transactions. The purpose of this research is to understand and apply the agreement clause between the seller and the buyer, as well as the seller's responsibility when default occurs in e-commerce transactions, especially through social media Instagram. The method in this research used a juridical normative library research method. This research method refers to legal norms in statutory regulations, court decisions, and legal norms that apply in society. The result of this research is that making buying and selling transactions through the Instagram social media platform has very limited responsibility compared to buying and selling transactions in the marketplace. this is because if the seller defaults on Instagram social media, the buyer will find it more difficult to ask for compensation from the seller. Keywords : Transaction, e-commerce, instagram